Catalogue of terminological authority for the analysis of documentary information from the university community of information units specialised in Social Sciences. - Matamoros Segura, Lucía (2006)
The results of the final graduation practice called "Catalogue of Terminological Authority for the analysis of the documentary information of the University Community of Information Units Specialized in Social Sciences (CUUICS)" are presented. It consisted of the revision, correction and normalization of the free vocabulary of the units of documentary information: Eugenio Fonseca Tortós Library of the University of Costa Rica, the Bibliographic Fund of the School of History and the Documentary Information Center of the Faculty of Social Sciences of the National University (Costa Rica).